Corporate actor networks in European policy-making : harmonizing telecommunications policy. - SCHNEIDER, Volker (1994)
Uses a case study approach using EC policy-making in the field of telecommunications to examine the structure and dynamics of EC policy processes, emphasizing the importance of supra- and transnational policy networks. The analysis demonstrated that a realistic concept of EC policy-making should not be limited to a one-level or two-level bargaining system but should integrate the whole network of corporate actors at the supranational, national and domestic level.